Should the Philippines Shift to the Opt-Out System? - Mabaquiao, Napoleon, Jr. (Animo Repository, 2024)
With the increasing demand for organs and the shortage of organ donations, more lives are being lost every day. Governments and national health authorities are, consequently, exploring more effective ways to increase organ donation rates, both from the living and the dead. Regarding cadaveric organ donations, the increase in organ donation rates in countries that have shifted from the opt-in (or explicit consent) system to the opt-out (or presumed consent) system has been very encouraging. As a result, some other countries still operating under the opt-in system are contemplating making the same move. In the Philippines, there are bills filed in the country’s legislative bodies proposing the shift from its current opt-in system to an opt-out system. This essay aims to assess the viability of this proposal in terms of its practical and moral soundness. It first examines the strengths and weaknesses of alternative organ donation systems in general based on the experiences of other countries. In light of the insights gathered from this examination, it then assesses the justifications advanced by proponents of the said proposal. On the whole, the paper shows that this proposal can only be practically and morally justified if the necessary supporting mechanisms are first put in place.